Resilient India: How modi transformed India$1 (Bs disaster management paradigms - Edited by Bluekraft Digital Foundation (New Delhi Rupa Publications, 2023)
It has not been long since the world faced the onslaught of COVID-19. Unprecedented in nature and scale, the pandemic, however, was just the latest calamity that people of India faced in its long and chequered history. More people were killed in the Bengal famine than in the twin nuclear strikes in Japan during the Second World War. The country has seen quakes, cyclones, tsunamis and even industrial disasters like the Bhopal Gas Tragedy. Yet, disaster management as a subject did not receive the attention that it deserved for long. However, post Kutch earthquake of 2001, things changed rapidly. The work done by the then Gujarat government under Narendra Modi altered forever the disaster management paradigm in the country. Disaster risk reduction is one area that is intertwined with the journey and experiences of Prime Minister Narendra Modi's life and work. On countless occasions, from Morbi floods of 1979 to Kutch quake in 2001, Modi worked on the ground to bring relief to the victims of disasters. As an administrator, he used these experiences to shape India's policies and turn it into a stronger and Resilient Nation. This book, through oral histories recounted by several individuals, covers the remarkable journey of India in this vital domain. Resilient India also offers practical insights based on Modi's experience for leaders in diverse domains on turning adversity into opportunity.
Keywords: Prime Minister; Disaster Management; Climate Change